Two methods for three - dimensional culture: addition of exogenous ECM components and capture of endogenous ECM components - McGinlay, Sarah (2023)
The culture of cells in hydrogels and scaffolds that mimic in vitro tissue has become increasing popular now there is an understanding of how important the role of ECM is in supporting and directing the behaviour of cells. As such there is a wide range of culture methods varying in complexity, that are available, each of which varies in complexity. From synthetic hydrogels with tuneable mechanical properties or natural (polysaccharide or protein) hydrogels that allow for natural interactions with ECM components, that more accurately represent the compisition of tissues and cells. This thesis looks at two different models of hydrogels, with opposite approaches. First, was an adipogenic model that used a top-down approach, where a native ECM protein (collagen) was used to form a natural hydrogel. Research into adipogenesis is important as obesity becomes more prevalent. Models that represent adipogenesis are important to combat the rise in obesity as they can become high content screening models for anti-obesity drugs. This model used an alginate fibre surrounding a collagen I core with mouse mesenchymal stem cells. Over the course of two weeks, this was found to be a viable model, that supported adipogenesis of mesenchymal stem cells. The creation of the fibre was simple, but requires optimisation to prevent alginate from blocking equipment.. The second model was developed using a bottom-up approach where synthetic self-assembling peptides were selected for the presence of a charge and then used to make a hydrogel. The peptide amphiphiles were designed to have increasing lysine residues (K2, K3 and K4) or a negative glutamic acid residue for a PA with a negative charge (E3). The presence of a charge was theorised to sequester native ECM components. Human induced pluripotent stem cells were in clusters on top of the range of PA hydrogels, a neutral hydrogel (FEFEFKFK) and Matrigel. This synthetic PA hydrogels (K2 and K3) sequestered a glycosaminoglycan secreted by human induced pluripotent stem cells. There was a change in cellular behaviour when cultured on hydrogels with different charges, there was increased attachment to the hydrogel on the negative PA (E3) hydrogel, than all others except Matrigel. There was also increased proliferation on the most positive PA (K4) hydrogel than all other hydrogels except Matrigel. Together this suggested that differently charged hydrogels may be able to create different ECM environments through the sequestration of natively secreted ECM components. The charged PA hydrogels have the potential to form a complex ECM with a large range of ECM components, that cannot be replicated by human design. In addition, the synthesised ECM components will be able to be modified by the cells throughout their lifetime, thereby replicating natural processes. This model could therefore be used to produce representative models for use in a wide range of systems many applications, for example drug testing, disease research and tissue regeneration.